2020
DOI: 10.37134/ibej.vol13.1.2.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Gallery Walk Teaching and Learning and Its Potential Impact on Students’ Interest and Performance

Abstract: Gallery Walk has the potential to improve the effectiveness of teaching and learning. Many teachers have especially been interested in using this strategy as a means of providing learning opportunities. This paper explores and discusses the definition of gallery walk, and the potential of this approach and its limitations. This article discusses the advantages of gallery walk and shows that researchers are still wondering on how gallery walk will help reaching the goals of a better learning, and how it will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…It makes them think and discuss together. In fact, the gallery walk strategy can stimulate communication among students and promote their critical thinking [5]. It has also been indicated that classroom management, student engagement, and student responsibility also can be improved by gallery walk strategy [7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It makes them think and discuss together. In fact, the gallery walk strategy can stimulate communication among students and promote their critical thinking [5]. It has also been indicated that classroom management, student engagement, and student responsibility also can be improved by gallery walk strategy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the gallery walk strategy can enhance the students' understanding of the teaching topics in a more pleasurable learning environment [5,7,12]. Furthermore, the simultaneous presence of the teacher and student in a clinical setting and discussions about the visited patients can better transfer the teacher's experiences to the students [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations